Affective Exercise Experience in Childhood and Psychological Determinants of Exercise Among Japanese Older Adults - Walker, Robert; Harada, Kazuhiro (Research Quarterly for Exercise and Sport, 2025)
Japan faces significant challenges associated with its super-aged society. Exercise and physical activity are recommended strategies to promote healthy aging and quality of life in older age. However, what determines exercise behavior among Japanese older adults is relatively unknown. The principle aim of this study was to explore exercise determinants and their relation to exercise behavior among Japanese older adults. Completed self-report questionnaires were received from 1,000 Japanese older adults aged between 65 and 74 years who resided in the Kansai area. A cross-sectional maximum likelihood path analysis was used to test the relationships between variables, where it was hypothesized that affective experiences in childhood had an indirect association with the exercise behavior of Japanese older adults through the seven psychological determinants of exercise. Demographic factors were also included in the model as potential influences of all factors. Knowledge held the largest significant direct association with exercise behavior (β =  .539, p = <.001), particularly more intense forms of exercise such as resistance exercise (β =  .725, p = <.001) and moderate to strenuous exercise (β = .420, p = <.001), whilst affective exercise experience in childhood (B = 3.749, p = <.001) and gender (B = 5.183, p = .003) held significant indirect associations. This paper emphasizes the importance of exercise-related knowledge among Japanese older adults and future research is warranted to further explore the role of positive affective exercise experiences in childhood and their influence on exercise behavior, especially amongst girls.